Biological and immunological characterization of norovirus major capsid proteins from three different genotypes. (January 2016) - Huo, Yuqi; Wan, Xin; Ling, Tong; Shen, Shuo
Abstract: Noroviruses (NoVs) are the leading cause of non-bacterial acute gastroenteritis worldwide. Due to a lack of cell culture system and animal model, our understanding of NoVs has been lagging behind. In this study, NoV major capsid proteins (VP1) from three different genotypes (GI.2, GII.3 and GII.4) were expressed by using recombinant baculovirus expression system and which led to successful assembly of virus-like particles (VLPs). The receptor binding patterns of three kinds of VLPs were characterized by using synthetic and salivary HBGA-VLP binding assay. Cross-reactivity and cross-blocking activity of rabbit hyperimmune sera against these VLPs were determined by ELISA/Western blot analysis and saliva-VLP binding blockade assay, respectively. Expression of the major capsid proteins from three genotypes all led to smaller VLPs in dominance when sf9 cells were cultured in suspension, which was in consistence with our previous report. These smaller VLPs were used for in vitro synthetic and salivary HBGA-VLP binding and binding blockade assays. VLPs from GII.3 strain exhibited no binding to all synthetic HBGAs and saliva samples tested while VLPs from GI.2 and GII.4 strain showed similar binding pattern and bound to all salivary HBGAs tested. Rabbit anti-GII.3 VLPs hyperimmune serum didn't block the binding of GI.2 and GII.4 VLPs to salivary HBGAs while rabbit anti-GI.2 VLP hyperimmune serum blocked the binding of GII.4 VLPs to salivary HBGAs but not vice versa. Our results provide further evidence indirectly in support of presence of other factors involved in receptor binding other than HBGAs for NoVs, and demonstrate poor cross-blocking activities of antibodies against VLPs within or across genogroups. Highlights: Suspension culture leads to dominance of smaller VLPs assembled. GII.3 VLPs exhibit no binding to all salivary and synthetic HBGAs tested. Our results demonstrate poor cross-blocking activities of antibodies against VLPs within or across genogroups.